The Influence of Contextual Teaching and Learning Strategy on Understanding Islamic Religious Education Lessons at PKPPS Subulussalam Ploso Surabaya - Amiruhadi, Amiruhadi; Hayumuti, Hayumuti; Muammar, M. Arfan (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2025)
The purpose of this study was to examine the implementation and realization of contextual learning strategies at PKPPS Subulussalam Ploso Surabaya and their influence on the quality of students' level of understanding in Islamic Religious Education (PAI) subjects. This study used a qualitative descriptive approach method by means of observation, direct interviews with educational experts and students, and documentation of research results. The results of the study indicate that, implicitly, the PAI learning process at PKPPS Subulussalam has implemented the principles of contextual learning. This strategy involves direct experience and role models by teachers, who are able to link teaching materials to real-life situations. This can improve students' understanding, especially in the internalization of Islamic values. The pesantren-based learning process that emphasizes real practice and role models also plays an important role in the success of this strategy. The research findings confirm that contextual learning has great potential to improve the effectiveness of Islamic religious education, especially in a multicultural environment. By combining learning materials with experience, learning becomes more relevant and meaningful. Therefore, this strategy can be used as an alternative learning model that supports improving the quality of understanding of Islamic values in the modern era.